2009
DOI: 10.1021/ja809683v
|View full text |Cite
|
Sign up to set email alerts
|

Non-Zinc Mediated Inhibition of Carbonic Anhydrases: Coumarins Are a New Class of Suicide Inhibitors

Abstract: The X-ray crystal structure of the adduct between the zinc metalloenzyme carbonic anhydrase II (CA, EC 4.2.1.1) with the recently discovered natural product coumarin derivative 6-(1S-hydroxy-3-methylbutyl)-7-methoxy-2H-chromen-2-one showed the coumarin hydrolysis product, a cis-2-hydroxycinnamic acid derivative, and not the parent coumarin, bound within the enzyme active site. The bound inhibitor exhibits an extended, two-arm conformation that effectively plugs the entrance to the enzyme active site with no in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
526
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 472 publications
(545 citation statements)
references
References 40 publications
17
526
0
2
Order By: Relevance
“…Similarly, systematic chemical proteomics studies 107,[111][112][113] have recently shown that another component of the extracellular matrix, periostin, exists in several splice isoforms that are abundantly found in most types of cancers [111][112][113][114] . 42,43 or using nanoparticles to design CAIs 44 . The first study linking the inhibition of CA9 with tumour shrinkage used the fluorescent sulphonamide (compound 1, n=1) and the cationic compound 2 (REF 28).…”
Section: Sulphonamides As Carbonic Anhydrase Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, systematic chemical proteomics studies 107,[111][112][113] have recently shown that another component of the extracellular matrix, periostin, exists in several splice isoforms that are abundantly found in most types of cancers [111][112][113][114] . 42,43 or using nanoparticles to design CAIs 44 . The first study linking the inhibition of CA9 with tumour shrinkage used the fluorescent sulphonamide (compound 1, n=1) and the cationic compound 2 (REF 28).…”
Section: Sulphonamides As Carbonic Anhydrase Inhibitorsmentioning
confidence: 99%
“…Alternative CAIs. Coumarins and thiocoumarins were only recently discovered to have carbonic anhydraseinhibiting properties, and their mechanism of inhibition has subsequently been deciphered 42,43 . The nat ural product 6-(1S-hydroxy-3-methylbutyl)-7-methoxy-2H-chromen-2-one (compound 10; FIG.…”
Section: Compound Genericmentioning
confidence: 99%
See 1 more Smart Citation
“…1−7 As shown by kinetic and X-ray crystallographic studies, coumarins are mechanism-based inhibitors that undergo hydrolysis under the influence of the zinc hydroxide, nucleophilically active species of the enzyme, with generation of substituted 2-hydroxycinnamic acids. 1,2 For example, the natural product coumarin A or the simple nonsubstituted derivative B (but also many of their congeners possessing various substitution patterns at the coumarin ring) 2 acts as an effective CAI against many of the mammalian isoforms CA I−CA XV known to date, and the real enzyme inhibitor was demonstrated to be the hydrolyzed coumarins, A1 and B1, formed from the original derivatives A and B, respectively (Scheme 1). 1,2 The adducts of CA II with coumarins A and B have been characterized by X-ray crystallography.…”
Section: ■ Introductionmentioning
confidence: 99%
“…1,2 For example, the natural product coumarin A or the simple nonsubstituted derivative B (but also many of their congeners possessing various substitution patterns at the coumarin ring) 2 acts as an effective CAI against many of the mammalian isoforms CA I−CA XV known to date, and the real enzyme inhibitor was demonstrated to be the hydrolyzed coumarins, A1 and B1, formed from the original derivatives A and B, respectively (Scheme 1). 1,2 The adducts of CA II with coumarins A and B have been characterized by X-ray crystallography. 1,2 These studies showed the 2-hydroxycinnamic acids A1 and B1 to be bound to the enzyme in an unprecedented way.…”
Section: ■ Introductionmentioning
confidence: 99%